Earthworms and Their Importance to Agricultural Soils in the Inland Pacific Northwest. Issue 1 (29th December 2020) - Kahl, Kendall B.; Johnson‐Maynard, Jodi L.
Abstract : Earthworms are important to the proper function of soils and in the cycling of organic matter to release nutrients for plant growth. An understanding of earthworm population size, number of years that active populations have existed, and types of earthworm species present in a field can help agricultural producers and their CCAs estimate the type and extent of potential impacts to the soil environment. Earn 1 CEU in Soil & Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/806 .